The Costs of Implementing the 1999 Canadian Asthma Consensus Guidelines Recommendation of Asthma Education and Spirometry for the Family Physician - Susan P Corrigan; David L Cecillon; Don D Sin; Heather M Sharpe; Elaine M Andrews; Robert L Cowie; SF Paul Man (Canadian Respiratory Journal)
BACKGROUND: National and international asthma guidelines recommend that patients with asthma be provided with asthma education and spirometry as a component of enhanced asthma care. The cost of implementing these interventions in family physician practices is not known.